Effects of manganese on microglia M1/M2 polarization and SIRT1‐mediated transcription of STAT3‐dependent genes in mouse. Issue 9 (21st May 2021) - Yan, Dongying; Gao, Liang; Lang, Jing; Gao, Xianhui; Ma, Honglin
Abstract: Overexposure to manganese (Mn) can lead to neurological diseases, characterized by behavioral and motor impairments. Microglia‐mediated neuroinflammation is involved in the pathogenesis and progression of neurodegenerative diseases. Microglial M1 and M2 phenotypes play pro‐inflammatory and anti‐inflammatory roles, respectively, in response to microenvironmental disturbances. Silent information regulator (SIRT1) has been demonstrated to play an important role in the neuroinflammatory response by deacetylating various transcription factors, such as proliferator‐activated receptor γ coactivator 1α (PGC‐1α), nuclear factor kappa B (NF‐κB), and signal transducer and activator of transcription 3 (STAT3). In addition, PGC‐1α and STAT3 have been implicated in microglial polarization and inflammatory response. In this study, Mn exposure (50, 100, 200 μmol/kg) induced neuroinflammatory injury and interfered with microglial M1/M2 polarization in mice, as indicated by the upregulated expression of M1 polarization marker mRNA ( IL‐1β, IL‐6, TNF‐α, and iNOS ), whereas changes in M2 polarization markers ( IL‐4, TGF‐β, and Arg1 ) varied, with some increasing and some decreasing, in response to increasing Mn doses, which was consistent with the flow cytometry results used to detect the percentages of each microglial type. We found that Mn could downregulate SIRT1 expression and activate NF‐κB signaling. Following mice in the 200 μmol/kg Mn treatment, STAT3 and PGC‐1α levels in the nuclear fraction both significantly decreased, and the interaction between the proteins decreased, affecting the transcription of STAT3‐mediated genes. These findings provide new insights regarding the role played by Mn neurotoxicity in the suppression of neuroinflammation through the regulation of microglial polarization.